2005
DOI: 10.1021/es0509836
|View full text |Cite
|
Sign up to set email alerts
|

Biorecovered Precious Metals from Industrial Wastes:  Single-Step Conversion of a Mixed Metal Liquid Waste to a Bioinorganic Catalyst with Environmental Application

Abstract: The complete and continuous reduction of 1 mM Cr(VI) to Cr(III) was achieved in a flow-through reactor using a novel bioinorganic catalyst ("MM-bio-Pd(0)"), which was produced by single-step reduction of platinum group metals (PGM) from industrial waste solution onto biomass of Desulfovibrio desulfuricans ATCC 29577. Two flow-through reactor systems were compared using both "MM-bioPd(0)" and chemically reduced Pd(0). Reactors containing the latter removed Cr(VI) for 1 week only at the expense of formate as the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
117
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 103 publications
(121 citation statements)
references
References 21 publications
4
117
0
Order By: Relevance
“…The waste biomasses from fermentation can be used (Orozco et al 2010) to recover catalytically-active precious metals from waste streams (i.e. this study) and also leachates made from PM scrap (Creamer et al 2006;Mabbett et al 2006;Murray et al 2007). The PEM fuel cell is made using a Bio-Pd anode (this study) and biohydrogen is fed (Macaskie et al 2005) to generate 68 mW of power per 16 cm 2 anode (Table 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The waste biomasses from fermentation can be used (Orozco et al 2010) to recover catalytically-active precious metals from waste streams (i.e. this study) and also leachates made from PM scrap (Creamer et al 2006;Mabbett et al 2006;Murray et al 2007). The PEM fuel cell is made using a Bio-Pd anode (this study) and biohydrogen is fed (Macaskie et al 2005) to generate 68 mW of power per 16 cm 2 anode (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that PMs can be bio-recovered from wastes and secondary sources with the resulting mixed-metal deposits on the bacterial cells being catalytically active (Mabbett et al 2006;Murray et al 2007). Therefore the second objective was to evaluate the activity of a PEM-FC made using PMs recovered from an industrial processing waste by a strain of E. coli previously shown to have potential for both H 2 production and for use as a FC catalyst (Orozco et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Palladium nanoparticles have been extensively studied both experimentally and theoretically mainly due to the excellent performance of the metal as a catalyst in hydrogenation and hydrogenolysis (Schuth and Reinhard 1998;Nishimura 2001). A recent development is the production of Pd nanoparticles supported on bacterial cells which show excellent potential as catalysts (Creamer et al 2007) in applications such as remediation of Cr(VI) (Mabbett et al 2006), chlorinated aromatic compounds (Baxter-Plant et al 2003;Redwood et al 2008), pesticides (Mertens et al 2007) and chlorinated organophosphates (Deplanche et al 2009), as well as major potential applications in "green chemistry" Wood et al 2010) and in clean energy Orozco et al 2010). The nanoparticulate nature of catalytically-active "Bio-Pd" was shown by surface area measurements ) while, using a magnetic method, Mikheenko et al (2001) showed the presence of nanoparticles of size ~ 5 nm.…”
Section: Introductionmentioning
confidence: 99%
“…A particularly environmentally beneficial aspect of such a biomass supported Pd catalyst is that it can be manufactured from waste. 18,19 We have shown previously that such a Bio-Pd 0 hybrid material is effective in the reductive dehalogenation of PCBs. 20 However, the previous analysis relied upon measurement of liberated chloride ion alone and hence detailed information on the breakdown products or the degradation pathway was not given.…”
Section: Introductionmentioning
confidence: 99%